Studies of Thorium(IV) Complexes of Schiff Base Derivad from Fluoroanline and p-(N,N'-Dicyanoethyl) Amino Benzaidehyde - Goyal, R.C.; arora, Kishor; Agarwal, D.D.; Sharma, K.P. (Asian Journal of Chemistry, 2010)
A series of new thorium(IV) complexes with a Schiff base derived from fluoroaniline and p-(N , N' -dicyanoethyl) amino benzaldehyde have been synthesized. Analytical, conductance, molecular weight and spectral data reveal that the complexes have the general composition (ThX4·nL)(X = NO3-, NCS-, n = 2; X =I- , n = 4; X = ClO4- , n = 6). Thorium atom is 6 or 10 coordinated depending upon the anions present in these complexes.